Efficient sugar production from sugarcane bagasse by microwave assisted acid and alkali pretreatment. (October 2016) - Zhu, Zongyuan; Rezende, Camila Alves; Simister, Rachael; McQueen-Mason, Simon J.; Macquarrie, Duncan J.; Polikarpov, Igor; Gomez, Leonardo D.
Abstract: Sugarcane bagasse represents one of the best potential feedstocks for the production of second generation bioethanol. The most efficient method to produce fermentable sugars is by enzymatic hydrolysis, assisted by thermochemical pretreatments. Previous research was focused on conventional heating pretreatment and the pretreated biomass residue characteristics. In this work, microwave energy is applied to facilitate sodium hydroxide (NaOH) and sulphuric acid (H2 SO4 ) pretreatments on sugarcane bagasse and the efficiency of sugar production was evaluated on the soluble sugars released during pretreatment. The results show that microwave assisted pretreatment was more efficient than conventional heating pretreatment and it gave rise to 4 times higher reducing sugar release by using 5.7 times less pretreatment time. It is highlighted that enrichment of xylose and glucose can be tuned by changing pretreatment media (NaOH/H2 SO4 ) and holding time. SEM study shows significant delignification effect of NaOH pretreatment, suggesting a possible improved enzymatic hydrolysis process. However, severe acid conditions should be avoided (long holding time or high acid concentration) under microwave heating conditions. It led to biomass carbonization, reducing sugar production and forming 'humins'. Overall, in comparison with conventional pretreatment, microwave assisted pretreatment removed significant amount of hemicellulose and lignin and led to high amount of sugar production during pretreatment process, suggesting microwave heating pretreatment is an effective and efficient pretreatment method. Highlights: Production of sugar was achieved in an efficient manner; maximum sugar yield (86%) in the pretreatment media was achieved in 7 min. Selective production of xylose and glucose was obtained by changing pretreatment media (NaOH/H2 SO4 ); yields are up to 22% and 64% respectively. Voids, holes and dismantled fibre bundles appeared on bagasse samples pretreated with NaOH under microwave condition, suggesting improved biomass digestibility. Severe acid conditions should be avoided, due to biomass carbonization, and reduced sugar release.